Porous venturi-orifice microbubble generator for oxygen dissolution in water - Liew, K.C.S. (MDPI AG, 2020)
Microbubbles with slow rising speed, higher specific area and greater oxygen dissolution are desired to enhance gas/liquid mass transfer rate. Such attributes are very important to tackle challenges on the low efficiency of gas/liquid mass transfer that occurs in aerobic wastewater treatment systems or in the aquaculture industries. Many reports focus on the formation mechanisms of the microbubbles, but with less emphasis on the system optimization and assessment of the aeration efficiency. This work assesses the performance and evaluates the aeration efficiency of a porous venturi-orifice microbubble generator (MBG). The increment of stream velocity along the venturi pathway and orifice ring leads to a pressure drop (Patm > Pabs) and subsequently to increased cavitation. The experiments were run under three conditions: various liquid velocity (QL) of 2.35â2.60 m/s at fixed gas velocity (Qg) of 3 L/min; various Qg of 1â5 L/min at fixed QL of 2.46 m/s; and free flowing air at variable QLs. Results show that increasing liquid velocities from 2.35 to 2.60 m/s imposes higher vacuum pressure of 0.84 to 2.27 kPa. They correspond to free-flowing air at rates of 3.2â5.6 L/min. When the system was tested at constant air velocity of 3 L/min and under variable liquid velocities, the oxygen dissolution rate peaks at liquid velocity of 2.46 m/s, which also provides the highest volumetric mass transfer coefficient (KLa) of 0.041 minâ1 and the highest aeration efficiency of 0.287 kgO2/kWh. Under free-flowing air, the impact of QL is significant at a range of 2.35 to 2.46 m/s until reaching a plateau KLa value of 0.0416 minâ1. The pattern of the KLa trend is mirrored by the aeration efficiency that reached the maximum value of 0.424 kgO2 /kWh. The findings on the aeration efficiency reveals that the venturi-orifice MBG can be further optimized by focusing on the trade-off between air bubble size and the air volumetric velocity to balance between the amount of available oxygen to be transferred and the rate of the oxygen transfer. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.